Muhammadiyah's Disaster Emergency Response during the 2025 Sumatra Floods and Landslides - Hamsaruddin, Dian Rahmana Putri; Mahmuddin; Andi Abdul Hamzah; Syamsuddin; Abdul Kahar (Universitas Islam Negeri Raden Intan Lampung, 2026)
Indonesia's high vulnerability to natural disasters necessitates a collaborative disaster governance framework that engages both state and non-state actors. This study examines Muhammadiyah’s emergency response to the large-scale floods and landslides that struck Aceh, North Sumatra, and West Sumatra beginning on 26 November 2025. Adopting a qualitative case study approach, the research draws on secondary data obtained from official reports, institutional publications, credible online media, and relevant scholarly literature. The data were analyzed using thematic content analysis to identify the organizational strategies, humanitarian interventions, and governance mechanisms employed during the emergency response. The findings reveal that Muhammadiyah played a pivotal role in disaster management by mobilizing its extensive institutional network, including the Muhammadiyah Disaster Management Center (MDMC), Lazismu, hospitals, schools, universities, mosques, and local branches. Humanitarian interventions encompassed volunteer deployment, logistics distribution, emergency shelter provision, healthcare services, psychosocial support, and Islamic philanthropic fundraising. The study demonstrates that Muhammadiyah has developed a distinctive faith-based disaster governance model that integrates institutional capacity, Islamic philanthropy, social solidarity, and religious values into coordinated humanitarian action. This model strengthens community resilience while complementing government-led disaster response efforts. By highlighting the strategic contribution of a faith-based civil society organization in emergency management, this study enriches the literature on collaborative disaster governance and offers practical insights into the role of religious organizations in enhancing disaster preparedness, response effectiveness, and societal resilience in disaster-prone countries.